Inside Front Cover: Exploiting molecular probes to perform near‐infrared fluorescence‐guided surgery (View 4/2020). Issue 4 (2nd December 2020) - Wu, Yifan; Zhang, Fan
Abstract : In article number 20200068, Fan Zhang and coworkers display that molecular probes with near‐infrared (NIR) fluorescence can visualize diseased tissue in deep penetration with improved signal‐to‐noise ratio, which considerably encourages the active participation of NIR fluorescence‐guided surgery in the operating room. This cover shows that tumors can be illuminated by fluorescent probes when light sheds on, while healthy tissue remains dark. In this way, surgeons can discriminate boundaries between lesions and healthy tissue under the real‐time guidance of NIR fluorescence imaging during surgery.